2012
DOI: 10.1111/j.1610-0387.2012.07857.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold plasma is well-tolerated and does not disturb skin barrier or reduce skin moisture

Abstract: All plasma treatments were well-tolerated and did not damage the skin barrier nor cause skin dryness. Cold plasma fulfils basic recommendations for safe use on human skin and as future option may serve as the first physical skin antiseptic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 19 publications
2
44
0
5
Order By: Relevance
“…Although there is increasing evidence that plasma treatment promotes the healing process of tissue and accelerates wound healing [18][21], [55], however the data reported here put forward the idea that argon plasma-treated liquids alter epithelial cell monolayer and impair cell adhesion. These are opposite evidences and should be discussed.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although there is increasing evidence that plasma treatment promotes the healing process of tissue and accelerates wound healing [18][21], [55], however the data reported here put forward the idea that argon plasma-treated liquids alter epithelial cell monolayer and impair cell adhesion. These are opposite evidences and should be discussed.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, cell physiological processes can be induced by plasma treatment that lead to increased tissue healing [18]–[20] but without disturbing e. g. the skin barrier or moisture [21]. In the healing process of tissues, the adhesion molecules of the cells play a crucial role for the cells' adhesion, migration and proliferation and are therefore, responsible for many cell functions [22][24].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely established use of plasma is for the sterilization of fragile materials sensitive to thermal damage. Subsequent studies have identified several clinical uses ranging from dental care to various skin diseases such as wound healing, foot fungus, and general hand sterilization without disturbing the skin barrier [2628]. In contrast to conventional lasers, which are based on thermal-mediated interactions with tissues that result in necrosis and permanent tissue injury, non-thermal plasmas operate at temperatures closer to room temperature to promote focal cell removal without inducing surrounding necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma species is one of the key parameters, because it influences the amount of species obtained as well as the energy consumed during the treatment of materials, such as film deposition 7,8 , surface sterilization 9 , polymers surface treatment 9 , dental and skin treatments 10 . This knowledge is of utmost importance not only to obtain better results in respective treatments, but also to offer minimal risk to the operator and user when used in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%